Cross-Cultural Harmony: Exploration of Multiculturalism in Islamic Society during the Age of the Prophet and Khulafaur Rasyidin - Siti Sumadiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article aims to examine the exploration of multiculturalism in Islamic society during the time of the Prophet and Khulafaur Rasyidin. This research concludes that: In the exploration of the multiculturalism of Islamic society in the era of the Prophet and Khullafaulr Rasyidin, it can be concluded that cross-cultural harmony created miracles in their lives. Diversity of ethnicities, cultures and social backgrounds is the main driver for unity and equality. This miracle not only creates tolerance, but also inspires positive collaboration between different individuals, forming an inclusive and strong society. This conclusion underlines that the understanding and application of multiculturalism values in past Islamic societies became an important foundation for harmony and continuity in collective life.